NADP-dependent glutamate dehydrogenases in a dimorphic zygomycete Benjaminiella poitrasii: purification, characterization and their evaluation as an antifungal drug target - Pathan, Ejaj K.; Kulkarni, Anand M.; Prasanna, Nallaballe V. L.; Ramana, V, Chepuri; Deshpande, V, Mukund (Biochimica Et Biophysica Acta-General Subjects, 2020)
Background: It has been reported that the genes coding for NADP-dependent glutamate dehydrogenases (NADP-GDHs) showed a cause-effect relationship with Yeast-Hypha (Y-H) reversible transition in a zygomycete Benjaminiella poitrasii. As Y-H transition is significant in human pathogenic fungi for their survival and proliferation in the host, the NADP-GDHs can be explored as antifungal drug targets. Methods: The yeast-form specific BpNADPGDH I and hyphal-form specific BpNADPGDH II of B. poitrasii were purified by heterologous expression in E. coll. BL-21 cells and characterized. The structural analogs of L-glutamate, dimethyl esters of isophthalic acid (DMIP) and its derivatives were designed, synthesized and screened for inhibition of NADP-GDH activity as well as Y-H transition in B. poitrasii, and also in human pathogenic Candida albicans strains. Results: The BpNADPGDH I and BpNADPGDH II were found to be homo-hexameric proteins with native molecular mass of 282 kDa and 298 kDa, respectively and subunit molecular weights of 47 kDa and 49 kDa, respectively. Besides the distinct kinetic properties, BpNADPGDH I and BpNADPGDH II were found to be regulated by cAMP-dependent- and Calmodulin (CaM) dependent- protein kinases, respectively. The DMIP compounds showed a more pronounced effect on H-form specific BpNADPGDH II and inhibited Y-H transition as well as growth in B. poitrasii and C. albicans strains. Conclusion: The present study will be useful to design and develop antifungal drugs against dimorphic human pathogens using glutamate dehydrogenase as a target. Significance: Glutamate dehydrogenases can be explored as a target against human pathogenic fungi.
Keywords: Antifungal compound; Benjaminiella poitrasii; Candida albicans; Dimethyl esters and amides of isophthalic acid; dimorphism; Enzyme inhibition; NADP-glutamate dehydrogenases

New 1,2,3-triazole-appended bis-pyrazoles: synthesis, bioevaluation, and molecular docking - Danne, Ashruba B.; Deshpande, V, Mukund; Sangshetti, Jaiprakash N.; Khedkar, Vijay M.; Shingate, Bapurao B. (ACS Omega, 2021)
The present work describes design of a small library of new 1,2,3-triazole-appended bis-pyrazoles by using a molecular hybridization approach, and the synthesized hybrids were evaluated for their antifungal activity against different fungal strains, namely, Candida albicans, Cryptococcus neoformans, Candida glabrata, Candida tropicalis, Aspergillus niger, and Aspergillus fumigatus. All the compounds exhibited broad-spectrum activity against the tested fungal strains with excellent minimum inhibitory concentration values. The molecular docking study against sterol 14 alpha-demethylase (CYP51) could provide valuable insights into the binding modes and affinity of these compounds. Furthermore, these compounds were also evaluated for their antioxidant activity, which also resulted in promising data.